An overview on recent advances in the synthesis of sulfonated organic materials, sulfonated silica materials, and sulfonated carbon materials and their catalytic applications in chemical processes - Sharghi, Hashem; Shiri, Pezhman; Aberi, Mahdi (Beilstein Journal of Organic Chemistry, 2018)
This review article discusses the progress related to the synthesis and catalytic applications of sulfonated organic materials, sulfonated silica materials, and sulfonated carbon materials for industrial and laboratory products. These catalysts are widely used in acid-catalyzed processes. Most of these acid catalysts are eco-friendly, reusable, and stable. Moreover, the discovery of unique catalysts is vital for developing new, efficient, and reusable catalysts for industrial and laboratory applications. The aim of this review article is to review the recent studies (2014–2018) in the ﬁeld of the utility of sulfonated organic materials, sulfonated silica materials, and sulfonated carbon materials for developing acidic catalysts.
Keywords: acid-catalyzed processes; biodiesel synthesis; sulfonated carbon materials; sulfonated industrial and laboratory products; sulfonated organic materials; sulfonated silica materials